Hydrogen and Fuel Cells: Innovations and Challenges (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
As a green and renewable energy source, hydrogen is considered one of the most important directions for future energy development, which has flourished globally in recent years and has broad market prospects. The large-scale utilization of renewable energy for hydrogen production cuts the cost of obtaining hydrogen. Furthermore, the continuous improvement of fuel cell technology and hydrogen storage technology strengthens the integration of hydrogen energy with smart grids and vehicles to reduce holistic carbon emissions and promote sustainable development. Conventional renewable energies, though with numerous merits, also have challenges associated with global hydrogen utilization, especially with the technologies of relevant hydrogen devices, such as fuel cells and electrolyzers.